Bibliometric Analysis: Utilization of Artificial Intelligence to Support Office Performance - Akbar, Rasona Sunara; Fathia, Vita Nurul; Hamdi, Muhammad Arif; Pujang, Seno Setya; Rosmaya, Mila; Bakhtiar, Masdar (Devotion : Journal of Research and Community Service, 2024)
Artificial Intelligence (AI) has experienced rapid development in recent years. In the current era of globalization, research on the use of AI to support the implementation of tasks has urgency to be raised in the scientific realm. This article aims to explore the study of the utilization of AI in the field of organizational performance. This study uses bibliometric analysis to review all articles related to the theme in the leading Scopus database. The search was carried out on Wednesday, March 13, 2024, at 16.50 WIB, and resulted in 13 documents related to "artificial intelligence" and "organizational performance" in 5 years (2019-2024). The results of this study show that the highest percentage of document types is in the form of articles, which reached 10 documents (76.9%), followed by conference papers as many as 2 documents (15.45%), and books as much as 1 document (7.7%). And the most frequently used languages in Artificial Intelligence and performance publications are English, Spanish, French, and Spanish. The research is based on a study conducted by T. Panichayakorn and K. Jermsittiparsert with the title "Mobilizing organizational performance through robotic and artificial intelligence awareness in mediating role of supply chain agility", 2019, Volume 8, Issue 5, Pages 757-768.